2015
DOI: 10.1371/journal.pone.0134131
|View full text |Cite|
|
Sign up to set email alerts
|

The Neural Basis of Typewriting: A Functional MRI Study

Abstract: To investigate the neural substrate of typewriting Japanese words and to detect the difference between the neural substrate of typewriting and handwriting, we conducted a functional magnetic resonance imaging (fMRI) study in 16 healthy volunteers. All subjects were skillful touch typists and performed five tasks: a typing task, a writing task, a reading task, and two control tasks. Three brain regions were activated during both the typing and the writing tasks: the left superior parietal lobule, the left supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Our results also showed that students in the HDKD group had lower scores in linguistic functions (including phonological decoding and morpho‐orthographic knowledge) compared to students in the HD‐only group. These results are not surprising, because at the initial stages, handwriting and keyboarding share linguistic skills (Higashiyama et al., 2015); thus, deficits in these linguistic functions may result in both handwriting and keyboarding difficulties.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our results also showed that students in the HDKD group had lower scores in linguistic functions (including phonological decoding and morpho‐orthographic knowledge) compared to students in the HD‐only group. These results are not surprising, because at the initial stages, handwriting and keyboarding share linguistic skills (Higashiyama et al., 2015); thus, deficits in these linguistic functions may result in both handwriting and keyboarding difficulties.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, given the fact that transcription skills require attention and motor functions, it is surprising that students with HDKD did not significantly differ from the students with HD alone in attention functions or sensory–fine–motor skills, specifically in the Finger Succession test, measuring kinesthetic abilities. A possible explanation for these results is that the behavioral measures underlying the handwriting execution process are different from those of keyboarding (Higashiyama et al., 2015), and need to be measured differently (i.e., via different tests). This finding was noted in previous studies (Preminger et al., 2004; Weintraub, Gilmour‐Grill, & Weiss, 2010) showing that among both elementary‐school students and young adults, handwriting and keyboarding skills vary in underlying perceptual and motor skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exner’s area has traditionally been associated with a role in the generation of motor commands for handwritten letters [23,25,59]. It has been repeatedly found to be more activated for writing than reading (-22,-4, 50) in Purcell, 2011, and (-24,-16, 68) in [60]. This region is involved in both handwriting and typewriting [26,60], suggesting its importance for written language production rather than specific motor commands per se, and is sensitive to word-length in spelling [27], which is consistent with our finding that it is more involved in Chinese writing than in English writing due to more complex written output.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly found to be more activated for writing than reading (-22,-4, 50) in Purcell, 2011, and (-24,-16, 68) in [60]. This region is involved in both handwriting and typewriting [26,60], suggesting its importance for written language production rather than specific motor commands per se, and is sensitive to word-length in spelling [27], which is consistent with our finding that it is more involved in Chinese writing than in English writing due to more complex written output. However recent work on stroke patients suggests that it may also have a role as a graphic buffer, a working memory component of the spelling system that temporarily holds the sequence of graphemes during production of letter names for oral spelling or letter shapes for written spelling [61].…”
Section: Discussionmentioning
confidence: 99%